Analisis Teori Antrian Terhadap Pelayanan Pangkas Rambut Abatasa di Pakupatan Kota Serang - Hasanah, Nur; Wiranti, Sovia; Ujang, M.; Hermawan, Bambang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study was conducted to evaluate the effectiveness of the service system at Abatasa Pakupatan Barbershop by applying the concept of queuing theory. The problems that emerged came from customer complaints regarding long waiting times when the number of visitors increased, as well as limited seating facilities because the service process was only handled by one barber. This study used a quantitative method with a descriptive analytical approach. Data collection was carried out through direct observation by recording customer arrival times and service duration. Data analysis used a Single Channel Single Phase queuing model with a First-Come, First-Served (FCFS) service rule. The results showed that the average customer arrival rate reached 25 people per day, while the service capacity was 30 people per day. The service facility utilization rate was recorded at 83.34%, with the chance of a server not serving a customer at 16.67%. The average number of customers waiting in the queue was around 4 people, with an average waiting time of 10 minutes, and the total time customers were in the system was around 12 minutes. Based on these findings, Abatasa Barbershop is advised to improve the quality and standards of service and carry out innovations to maintain customer satisfaction and loyalty amidst increasingly competitive business competition.